Emotional Responses to Visual Art and Commercial Stimuli: Implications for Creativity and Aesthetics - Cheung, Mei-Chun; Law, Derry; Yip, Joanne; Wong, Christina W. Y. (Frontiers in Psychology, 2019)
There is an ongoing debate about whether emotional responses to artworks are similar to those produced by the commercial stimuli experienced in everyday life. In this study, we evaluated the emotional responses to the visual art and commercial stimuli by using electroencephalography (EEG) to obtain an objective measure of emotional responses of the brain, namely the frontal alpha asymmetry. Positive frontal alpha asymmetry suggests positive emotional responses, and vice versa. The visual art stimuli consisted of 80 artistic and naturally colored paintings whereas the commercial stimuli consisted of 80 different window displays of fashion collections. The results revealed that positive frontal alpha asymmetry was elicited when the participants judged the visual art stimuli as either beautiful or not beautiful. For the commercial stimuli, positive frontal alpha asymmetry was observed when they were considered as beautiful, whereas negative frontal alpha asymmetry was exhibited towards those perceived as not beautiful. These findings suggest more positive emotional responses to the visual art stimuli, regardless of their aesthetics. However, favorable emotional responses were only elicited towards the commercial stimuli regarded as beautiful. The implications for the creative and aesthetic design of the commercial stimuli in Chinese society in influencing consumers’ emotional responses are discussed.